Creating and optimizing client-server applications on mobile devices - Anacleto, Ricardo (2015)
Mobile devices are embedded systems with very limited capacities that need to be considered when developing a client-server application, mainly due to technical, ergonomic and economic implications to the mobile user. With the increasing popularity of mobile computing, many developers have faced problems due to low performance of devices. In this paper, we discuss how to optimize and create client-server applications for in wireless/mobile environments, presenting techniques to improve overall performance.